The Impact of Social Media Usage on Product and Service Sales Growth - Evelyn, Fedyanti Yoan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Sabda Setia, 2025)
This study aims to analyze the influence of Social Media Usage and Digital Marketing Strategies on sales growth, specifically investigating the mediating role of Consumer Trust among MSME actors. The main issue addressed is the inconsistency of the direct link between social media activity and sales performance, suggesting the necessity of an intervening mechanism. A quantitative approach was employed, using a survey method involving 100 MSME respondents. Data analysis was conducted using multiple linear regression. The results show that Digital Marketing Strategies and Consumer Trust individually have a significant influence on sales growth. However, the direct influence of Social Media Usage alone was found to be non-significant. Collectively, the model explains 78% of the sales growth variation. Crucially, Consumer Trust is proven to function as a Full Mediating variable, meaning the influence of social media must completely pass through trust to increase sales. This finding emphasizes that strategic investment in transparent and responsive digital practices, focused on building trust, is the key driver for sales, rather than merely post quantity.